2021
DOI: 10.1556/2006.2020.00088
|View full text |Cite
|
Sign up to set email alerts
|

Gambling disorder is associated with reduced sensitivity to expected value during risky choice

Abstract: Background and aimsIndividuals with gambling disorder display increased levels of risk-taking, but it is not known if it is associated with an altered subjective valuation of gains and/or losses, perception of their probabilities, or integration of these sources of information into expected value.MethodsParticipants with gambling disorder (n = 48) were compared with a healthy comparison group (n = 35) on a two-choice lottery task that involved either gains-only or losses-only gambles. On each trial, two lotter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 46 publications
2
21
0
Order By: Relevance
“…From an economic perspective, to decide whether and how much to gamble, people need to integrate probabilistic information (probability and reward magnitude) under conditions of risk (where this information is known-e.g., with a roulette wheel) or uncertainty (where this information is not known-e.g., sports betting) [37]. Accordingly, as prospect theory [12,13] is the most influential descriptive theory of decision-making under risk and uncertainty, and caters for individual difference in probability and value weighting, it has been used as a tool to explore problem gambling.…”
Section: Problem Gamblers' Risk Preferencesmentioning
confidence: 99%
See 1 more Smart Citation
“…From an economic perspective, to decide whether and how much to gamble, people need to integrate probabilistic information (probability and reward magnitude) under conditions of risk (where this information is known-e.g., with a roulette wheel) or uncertainty (where this information is not known-e.g., sports betting) [37]. Accordingly, as prospect theory [12,13] is the most influential descriptive theory of decision-making under risk and uncertainty, and caters for individual difference in probability and value weighting, it has been used as a tool to explore problem gambling.…”
Section: Problem Gamblers' Risk Preferencesmentioning
confidence: 99%
“…Problem gambling is a general term used widely in research to encompass compulsive gambling, addictive gambling, and gambling disorder [38]. In the Diagnostic and Statistical Manual of Mental Disorders (DSM-5), gambling disorder is regarded as a behavioural addiction which has a prevalence of approximately 0.2% to 0.3% in the general population, and is associated with 'continued gambling in the face of mounting losses, often at the detriment of financial, social and occupational obligations' [37] (p. 1).…”
Section: Problem Gamblers' Risk Preferencesmentioning
confidence: 99%
“…Moreover, trait individual differences in cardiac perception have been linked to a number of cognitive and affective phenomena, including time perception, anxiety and depressive symptoms, emotional reactivity and memory, alexithymia, as well as intuitive decision-making (Verdejo-Garcia et al, 2012). Of note, several of these dimensions are affected in subjects with GD (Bibby & Ross, 2017;Di Nicola, Pepe et al, 2020;Limbrick-Oldfield et al, 2020;Pettorruso et al, 2019;Rogier & Velotti, 2018), consistent with a key role of interoceptive processes in addictive disorders.…”
Section: Discussionmentioning
confidence: 88%
“…Lottery gambling is relatively inexpensive to play compared to other gambling activities, and it offers attractive jackpot prizes (the odds of winning are very low, but under-estimated by most players). The available studies suggest that lottery players are distinct from nonplayers (Limbrick-Oldfield et al, 2021), that addicted lottery gamblers could exhibit a phenotype different from individuals with other gambling types (McGrath et al, 2018), and that different clusters can be identified among treatment-seeking patients who report problems related to lottery gambling (Challet-Bouju et al, 2015;Granero, Jimenez-Murcia, et al, 2020;Granero, León-Vargas, et al, 2020). But little research has been devoted to lottery tickets playing compared to other gambling forms, and only a few studies focus on the aspects of this gambling activity with the aim to identify its underlying profile/s, its specific risk factors, and the concrete clinical expressions and consequences.…”
Section: Lottery Gamblingmentioning
confidence: 99%